2020
DOI: 10.1108/edi-09-2018-0158
|View full text |Cite
|
Sign up to set email alerts
|

Is diversity debate farfetched? Psychological contract expectations, performance and intention to stay

Abstract: PurposeThe purpose of the study is to understand whether psychological contract (PC) expectations manifest differently for diversity clusters of gender, physical disability and region in relation to job performance and intention to stay.Design/methodology/approachIt is a survey-based study. Data from 1,065 information technology and busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…Intention to stay has also been studied in relation to job satisfaction and demographic variables. As such, in the study of the generation Y employees working within the information technology and business process management (IT/BPM) industry, it was revealed that there was no significant relationship found between gender and intention to stay (Pant and Venkateswaran, 2020). On the contrary, Sokmen and Ekmekcioglu (2016) found that there was a significant relationship between gender and intention to stay.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intention to stay has also been studied in relation to job satisfaction and demographic variables. As such, in the study of the generation Y employees working within the information technology and business process management (IT/BPM) industry, it was revealed that there was no significant relationship found between gender and intention to stay (Pant and Venkateswaran, 2020). On the contrary, Sokmen and Ekmekcioglu (2016) found that there was a significant relationship between gender and intention to stay.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the surge in the Indian economy since 2005, Indian women are entering the workforce in large numbers but face multiple workplace challenges. Women constitute 48.5% of India's population but still have the lowest representation in the workforce among the Asia–Pacific regions (Pant and Venkateswaran, 2020; Singh and Pandey, 2019). Deeply entrenched patriarchal value systems, safety considerations, the primary burden of household work, encouragement to leave jobs after marriage or childbirth and exclusion from informal networks exert covert pressure on women professionals in the industry (Chakraborty and Chatterjee, 2020; Singh and Pandey, 2019).…”
Section: Gender Representation At the Indian Workplacementioning
confidence: 99%
“…Deeply entrenched patriarchal value systems, safety considerations, the primary burden of household work, encouragement to leave jobs after marriage or childbirth and exclusion from informal networks exert covert pressure on women professionals in the industry (Chakraborty and Chatterjee, 2020; Singh and Pandey, 2019). The Indian social norms “condition women to believe that they cannot be a good wife, mother, and manager all at the same time” (Pant and Venkateswaran, 2020, p. 644).…”
Section: Gender Representation At the Indian Workplacementioning
confidence: 99%
See 2 more Smart Citations